2020
DOI: 10.31219/osf.io/cjrwt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Literary Work as Authentic Material for the EFL Classroom in Indonesia

Abstract: Literary work can be used as authentic material in the EFL classroom to achieve the language development of the learners. This study aims to discuss the role of literary texts and the benefits of using the texts for the EFL classroom. The study was conducted at the English Education Study Program, Bandar Lampung University, Indonesia. The reasons in choosing specific literary texts in the EFL classroom are evaluated and the main criteria to select the literary texts are discussed such as the motivation and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The findings show that exploited case studies can foster critical awareness, critical reading skills as well as the authenticity of texts and class assignments. It is also supported by other previous studies that discuss the role of literary texts and the benefits of using the texts in the EFL classroom (Nanda & Susanto, 2020). It is found that the texts can facilitate the enjoyment of the learners while they are learning.…”
Section: Text Exploitation In the Classroomsupporting
confidence: 81%
“…The findings show that exploited case studies can foster critical awareness, critical reading skills as well as the authenticity of texts and class assignments. It is also supported by other previous studies that discuss the role of literary texts and the benefits of using the texts in the EFL classroom (Nanda & Susanto, 2020). It is found that the texts can facilitate the enjoyment of the learners while they are learning.…”
Section: Text Exploitation In the Classroomsupporting
confidence: 81%
“…Even though exploited text is very useful in learning reading in class. As stated by the previous study that discussed the role of literary texts and the benefits of using the texts for the EFL classroom (Nanda & Susanto, 2020). It is found that the texts can facilitate the enjoyment of the learners while they are learning.…”
Section: Text Exploitation In the Classroommentioning
confidence: 83%
“…Based on observations, questionnaires and interviews, the students mostly agreed that the animated video enriched knowledge, vocabulary, grammar and pronunciation. This can be observed further to explore how their interests and motivations are (Nanda & Susanto, 2021). The students also said that watching cartoon movies as a learning media can be a lot of fun for them.…”
Section: Discussionmentioning
confidence: 94%
“…Although listening practice is difficult, it is highly recommended for every student to practice English listening by enjoying such as watching movies, listening to songs, and others (Nanda & Susanto, 2020). Listening is also related to someone's memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation